HEMORRHAGIC OCCLUSIVE RETINAL VASCULITIS AND NONHEMORRHAGIC VASCULITIS AFTER UNCOMPLICATED CATARACT SURGERY WITH INTRACAMERAL VANCOMYCIN. (2017) - Ehmann, David S.; Adam, Murtaza K.; Kasi, Sundeep K.; Sivalingam, Arunan; Dunn, James P.
Abstract : Purpose: To describe two cases of vasculitis: one hemorrhagic and one nonhemorrhagic after uncomplicated cataract surgery with intracameral vancomycin. Methods: Retrospective case series. Results: A 74-year-old female and a 54-year-old female developed severe visual loss within 2 weeks of uncomplicated cataract surgery with intracameral vancomycin. The first patient developed a fulminant hemorrhagic vasculitis, whereas the second patient developed a less severe nonhemorrhagic vasculitis. Partial visual recovery and prevention of neovascular glaucoma was achieved using a combination of topical, oral, and intravitreal corticosteroids, along with intravitreal antivascular endothelial growth factor agents in the first patient and a combination of topical and oral corticosteroids alone in the second patient. Conclusion: Hemorrhagic occlusive retinal vasculitis and nonhemorrhagic vasculitis after uncomplicated cataract surgery with intracameral vancomycin have been rarely reported. Early recognition and treatment may prevent devastating visual outcomes. Abstract : The authors report two cases of vasculitis: one hemorrhagic and one nonhemorrhagic after uncomplicated cataract surgery with intracameral vancomycin. Early recognition, diagnosis, and treatment are required to prevent the development of neovascular glaucoma. The authors report successful treatment using a combination of topical, oral, and intravitreal corticosteroids, along with intravitreal antivascular endothelial growth factor agents.